2002
DOI: 10.1021/jf010812u
|View full text |Cite
|
Sign up to set email alerts
|

An LC-MS Method for Analyzing Total Resveratrol in Grape Juice, Cranberry Juice, and in Wine

Abstract: Resveratrol is an antioxidant found in grapes, grape products, and some other botanical sources with antiinflammatory and anticancer properties. In grapes and wine, it occurs both as free resveratrol and piceid, the 3beta-glucoside of resveratrol. Here we report a liquid chromatography-mass spectrometry method to analyze total resveratrol (including free resveratrol and resveratrol from piceid) in fruit products and wine. Samples were extracted using methanol, enzymatically hydrolyzed, and analyzed using rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
184
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(195 citation statements)
references
References 19 publications
6
184
1
4
Order By: Relevance
“…The corona voltage was 10 V and the cone voltage was of 150 V. Nitrogen was used as desolving and nebulizing gas with flow rates of about 300 L/h and 50 L/h, respectively. APCI mass spectra were recorded over the range m/z 140-600 in a scan time of 1 s (Wang et al 2002). For system control and data processing, Mass Lynx software (Micromass) was used.…”
Section: Ms Analysis Of Resveratrolmentioning
confidence: 99%
“…The corona voltage was 10 V and the cone voltage was of 150 V. Nitrogen was used as desolving and nebulizing gas with flow rates of about 300 L/h and 50 L/h, respectively. APCI mass spectra were recorded over the range m/z 140-600 in a scan time of 1 s (Wang et al 2002). For system control and data processing, Mass Lynx software (Micromass) was used.…”
Section: Ms Analysis Of Resveratrolmentioning
confidence: 99%
“…Resveratrol is a naturally occurring polyphenolic phytoalexin [51]. Foods known to contain resveratrol are limited to grapes, wine, grape juice, cranberries, cranberry juice [52,53], peanuts, and peanut products [54]. It has shown that the roots of the weed Polygonum cuspidatum constitute one of the richest sources of resveratrol [55].…”
Section: Phytochemicals Skin Cancer and Rosmentioning
confidence: 99%
“…Numerous methods have been published for determining trans-resveratrol in liquid matrices such as grape juice, wine, urine, plasma, or blood 1,2,14,15,18,28,[30][31][32]34 . Most of them are direct analyses 1,2,15,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Most of them are direct analyses 1,2,15,18 . In the case of liquid extraction, ethyl acetate is often used 14,32 . The extract is further analyzed by HPLC hyphenated to UV absorption 8,19,21 , fluorescence 17 , or mass spectrometry 3,32 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation